IRIIE2012 Poster: Islamic economics themes in the strategic planning of mergers and acquisitions in the Malaysian construction industry - Sarif, Suhaimi Mhd; Ismail, Yusof (2012)
This poster presents Islamic economics themes in strategic planning for mergers and acquisitions in the Malaysian construction industry. It provides dedicated focus, direction and commitment to organizations to achieve their goals effectively and efficiently. In a competitive market, every firm tries to minimize cost by being efficient so that it can optimize potentials and competitive positions. The research questions are: (a) What are the Islamic economic factors that firms in the construction industry need to consider when adopting M&A strategy in the construction industry, and (b) What is the degree of the importance of each of the factors mentioned? The study conducted personal interview with the 11 construction managers. The results of personal interviews gave five Islamic themes, namely (1) Unity of God (tawhidic) paradigm, (2) justice (‘adl), (3) trust (amanah), (4) promoting good governance-prevention eveil (amr bil ma’aruf nahi anil mungkar), and (5) vicegerency (khalifah) that supported M&A strategy. In terms of practical implications, this study facilitates strategists or planners with common guidelines to plan strategically for M&A. The study suggests the future research to use mixed method (questionnaire survey and personal interview) and include more informants, particularly industry key stakeholders.